380 Multiple pesticide exposures and the risk of multiple myeloma in Canadian men. (11th October 2013) - Kachuri, L K; Demers,; Blair,; Spinelli,; Pahwa,; McLaughlin,; Dosman,; Pahwa,; Harris,
Abstract : Objectives: Multiple myeloma (MM) has been linked to certain agricultural exposures, including pesticides, however the effects of exposure to multiple pesticides have not been explored. This analysis investigated the association between self-reported use of multiple pesticides and MM risk. Commonly used pesticide combinations and interactive effects were also assessed. Methods: A frequency matched population-based case-control study was conducted among men in 6 Canadian provinces between 1991 and 1994. Data from 342 MM cases and 1506 controls were analysed using logistic regression to calculate odds ratios (OR) and 95% confidence intervals (CI). Pesticides were grouped by type, chemical class and carcinogenicity. Carcinogenic probability values were created using evaluations from the International Agency for Research on Cancer and U. S. Environmental Protection Agency. Regression models were adjusted for age, province of residence, use of proxy respondents, smoking, and selected medical history variables. Trends were examined using ordinal variables. Commonly used pesticide combinations were assessed for interaction on the additive scale using the interaction contrast ratio (ICR). Results: Multiple pesticide use was not associated with monotonically increasing odds of MM, although positive trends were observed for "probably" carcinogenic pesticides (ptrend = 0.01), insecticides (ptrend = 0.07), and fungicides (ptrend = 0.05). Higher odds of MM were observed among men who reported using at least one carbamate pesticide (OR = 1.99, 95% CI: 1.19–3.33), one phenoxyherbicide (OR = 1.60, 95% CI: 1.11–2.30), 3 or more "probably" carcinogenic pesticides (OR = 2.14, 95% CI: 1.01–4.52), and 3 or more organochlorines (OR = 2.26, 95% CI: 1.07–4.78). Investigating commonly used pesticide combinations, revealed increased odds among men who used both chlordane and mecoprop (OR = 2.18, 95% CI: 1.12–4.27; ICR = 0.63). Conclusions: Focusing on multiple pesticides is important because this more accurately reflects how exposures occur in occupational settings. Although the overall pattern of results was complex, excess risks observed for certain pesticide types and chemical classes suggest these may be MM risk factors.